Enzymatic degradation of deoxynivalenol by a novel bacterium, Pelagibacterium halotolerans ANSP101. (June 2020) - Zhang, Jing; Qin, Xiaojuan; Guo, Yongpeng; Zhang, Qiongqiong; Ma, Qiugang; Ji, Cheng; Zhao, Lihong
Abstract: Deoxynivalenol (DON), a toxic secondary metabolite produced by Fusarium species that mainly infests cereals such as wheat and corn, threatens human and livestock health. The present study describes the characterization of a novel bacterial strain, Pelagibacterium halotolerans ANSP101 which is capable of transforming DON to less-toxic product 3-keto-deoxynivalenol by the oxidation of the C3 hydroxyl group. Strain ANSP101 was isolated from a seawater sample from a depth of 55 m in Chinese Bohai sea. The strain was identified as Pelagibacterium halotolerans by morphology characterization and 16S rDNA gene sequencing. The DON degrading activity of strain ANSP101 was predominantly attributed to the bacterial cell lysate. Besides, the cell lysate was sensitive to sodium dodecyl sulfate, heat, and proteinase K treatment, indicating that the intracellular proteins or enzymes are responsible for the DON degradation. The optimal temperature and pH for the maximal degradation of DON were 40 °C and pH 8.0 by the cell lysate. These results provide the potential use of P. halotolerans ANSP101 as a detoxification agent for DON decontamination in cereals and feed. Highlights: A novel bacterium, Pelagibacterium halotolerans with DON-degrading ability was isolated. The metabolite of DON was identified as 3-keto-deoxynivalenol. The cell lysate presented degradation ability over a broad range of temperatures and pH. The degradation progress was enzymatic.